PERAN PEREMPUAN MINANGKABAU UNTUK MENUNJANG PEREKONOMIAN KELUARGA TAHUN 1912-1921 DALAM SURAT KABAR SOENTING MELAJOE - Fajri Mulyani, Fini; Syahriani, Fadilla (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
This research aims to analyze the role of Minangkabau women in supporting the family economy in 1912-1921 as reviewed from the Soenting Melajoe newspaper. This research applies a historical approach by following 3 phases, namely heuristics, source criticism, and historiography. The findings from this research indicate that the contribution of Minangkabau women in improving prosperity, especially in the economic sector, is reflected in the role of women in the period 1912-1921. In the field of family economics, women manage household finances, even though they are faced with a lack of confidence in their abilities. Outside the family environment, women are involved in earning a living through various professions such as craftsmen, teachers, traders, journalists and government employees. They are also active in developing skills and involved in education to achieve economic prosperity. Their participation reflects the economic transformation during the modernization of Minangkabau society, driven by education, skills and the active role of women in economic life.